Echando raíces : producción y alimentos (2018)
"This document compiles the research that allowed the subsequent development of the design proposal, which is explained in the final part of the paper. The document was developed for the subject Estudio 8: Proyecto de grado for the Universidad de los Andes. It presents a research development around the methods of agricultural production and the relationship between food and consumers that are seeking for alternative production methods that allow them to be near to the source of their foot and that have less impact on their environment and their health. After analyzing the local context and user concerns, a design proposal was developed, which consists of a learning system that promotes the ecological farming in urban spaces, where the consumer is able to produce his own food, can also exchange acquired knowledge and be benefited physically and emotionally." -- Tomado del Formato de Documento de Grado.